Allmänhetens informationsbehov före och vid ett eventuellt dammbrott i Lule älv - Reiser, Pernilla (2013)
The likelihood that a dam break would occur in Lule River is estimated to be very low, but the consequences would be significant if it would happen. The purpose of this thesis is to examine the need for information of the residents in Porjus and Boden, before and at the time of a possible dam break in Lule River. The specific questions addressed were: Do the residents want information and, if so, what kind of information do they want before and at the time of a dam break? In what way do the residents want to be informed at the time of a dam break? How high is the resident’s confidence in Vattenfall, the municipalities, the County Administration Board of Norrbotten, and media? Is it important for the residents whom information comes from before and at the time of a dam break? How do the residents judge the risks and the effects of a dam break? Are the residents worried that a dam break will occur? Is there a difference between genders or residents of each location? Does the responsibility of Vattenfall, the County Administration Board of Norrbotten, and the municipalities comply with the residents’ perception of what the authorities are responsible of in case of a dam failure? A questionnaire was sent out to randomly selected residents in Porjus and Boden. Telephone interviews were conducted with representatives for Vattenfall Vattenkraft AB and the municipalities of Gällivare, Jokkmokk, Boden, and Luleå. The results show that the residents wanted to know how much water there would be at a dam break, how much time they would have to evacuate, what areas would be affected, appropriate escape-routes, and where to go in case of a dam break. The residents had high confidence in Vattenfall Vattenkraft AB and the County Administration Board of Norrbotten, but a bit lower confidence in the municipalities. The majority of residents were not worried at all that a dam break would occur, except for some women in Boden. A large percentage of the residents were not prepared for a dam break and had none, or little control, ...